Model Hubungan Alih Daya Dalam Hukum Ketenagakerjaan Indonesia Ditinjau Dari Perspektif Keadilan - Sukhebi s.; Atma Suganda; Ismail I (Postgraduate of Jayabaya University, 2020)
This study intends to examine what prioritizes legal certainty for the guarantor of the debtor in the event of bankruptcy. This study will also discuss the practice of the methods used by personal guarantees to escape the snares of bankruptcy proposed by creditors as regulated in Article 24 paragraph (2) of the UUKPKPU, due to the lack of regulation in the UUKPKPU regarding guarantors. The method used in this research is the juridical-normative method. The results of this study indicate the following conclusions. First, the fact of the bankruptcy of the guarantor in various cases illustrates the incompatibility of the practice (das sein) of personal guarantees and the theory of underwriting. If the guarantor goes bankrupt, then the guarantor is no longer the party assisting the debtor; but it takes too much responsibility. Supported by the contents of the borghtoct agreement which does not contain provisions regarding the position of the guarantor in the event of debtor bankruptcy. If suddenly the guarantor goes bankrupt, then the theory of the purpose of bankruptcy which is to divide the principal debtor's assets will certainly not be achieved (especially when it is only the guarantor's property) is not achieved and finally legal certainty does not materialize. Second, the effort to realize legal certainty for creditors and guarantors in bankruptcy is the regulation of legal rules that regulate bankruptcy in a more detailed and rigid manner, in which the bankruptcy law consists of elements of general civil law (KUHPerdata), the Law on Bankruptcy, jurisprudence and other regulations. related regulations.